The Impact of Transnational Migrant Knowledge Transfer on National Tourism Development: A Case Study of Ghana - Tackie, Michael Kojoe Amoah; Mensah, Thelma Frimpong; Awadzie, David Mensah (International Journal of Business, Management and Economics, 2024)
The primary objective of this study is to investigate the impact of transnational migrant knowledge transfer on national tourism development in Ghana. A survey research approach was employed to gather data from the DuBois Center and Diaspora African Forum in Accra to achieve this aim. The study examined two hypotheses using partial least squares structural equation modeling (PLS-SEM). The findings, which indicate that transnational migrant knowledge transfer positively and statistically significantly affects national tourism development, underscore the critical role of transnational migrant knowledge transfers in enhancing the tourism sector. The study's urgent recommendations for policymakers, as key stakeholders, to create a supportive policy environment encouraging investments to enhance national tourism development, focusing on incentives for migrant investors in the tourism sector, are of immediate importance